Falcon Research in Greenland, 1973 - Burnham, William A.; Ward, F. Prescott; Mattox, William G.; Clement, David M.; Harris, James T. (ARCTIC, 1974)
. During the summer of 1972 a research team initiated the first in-depth study of the peregrine falcon (Falco peregrinus) in West Greenland. Eight eyries (nests) of this endangered species were located in an inland sample area of 700 sq. mi. Detailed observations were taken of peregrine breeding behaviour at one eyrie. Seven of the eyries produced young, containing an average of 2.57 young per successful eyrie. This high reproductive rate indicates a healthy population, but analyses of 2 addled eggs revealed high p,p'-DDE as well as polychlorinated biphenyl (PCB) residues and eggshell fragments from 9 eggs showed a 14 per cent decrease in thickness compared with 42 eggs collected in Greenland before the introduction of DDT into the environment. . The [1973] survey area consisted of 900 sq. mi. (2,330 sq. km.), including ice-cap, lakes, fjords, and other unsuitable habitat totalling about 150 sq. mi. (388 sq. km.). We found 10 occupied peregrine falcon nesting cliffs in the survey area in 1973. . 9 eyries produced young. Of these 9, 7 were also successful in 1972, while another was occupied throughout the season by an aggressive pair, and at the ninth a lone female mildly defended the cliff. Of the 9 producing eyries in 1973, 1 contained 4 young, 5 contained 3 young each, 2 had 2 young each, and 1 held 1 young. This gives a total of 24 young peregrines and a production rate of 2.4 young per occupied eyrie, or 2.67 young per successful eyrie. These young were counted at advanced ages varying from 2.5 weeks to just before fledging. It is believed that all or almost all fledged. We found 1 occupied eyrie per 90 sq. mi. (233 sq. km.), or 1 successful eyrie per 100 sq. mi. (260 sq. km.). All young were banded with a metal band on the left tarsus and a red plastic band on the right. . The colour bands signify the beginning of an international peregrine colour banding system established for quick geographical identification of banding locality. During the 2 summers, 9 gyrfalcon nesting cliffs were located in the survey ...